Strategi Komunikasi Pemasaran pada Media Sosial Akun Tik Tok @Hedonestate - Kalenia Lailia Rahmawati; Ignasius Liliek Senaharjanta (Lembaga Pengembangan Kinerja Dosen, 2025)
TikTok has become one of the most popular social media platforms with more than 2 billion monthly active users. This makes TikTok a very potential digital marketing tool for various brands and products. One of those TikTok accounts is @hedonestate, an account from a culinary brand that is currently a hit among generation Z with more than 40 thousand followers. This research aims to formulate the right content and engagement management strategy on the @hedonestate TikTok account in order to increase brand awareness and sales of promoted products. The research method used is a qualitative approach with a case study on the @hedonestate account. Data collection is carried out through in-depth interviews with the @hedonestate account manager and a number of his followers, as well as content analysis of the 50 latest TikTok videos uploaded to the account. The data obtained is then analyzed qualitatively to produce content strategy recommendations that are in accordance with the Elaboration Likelihood Model theory, as well as engagement strategies to increase user engagement such as the number of likes, comments, and shares so that it has the potential to encourage product purchase decisions. The results of this research are expected to provide recommendations for effective social media marketing management strategies on the TikTok account @hedonestate, so that it can increase brand awareness and sales of promoted products.